Castigat ridendo moris’? Persius’ view from his satires to the entire Roman Principate in the first century of the Christian era - Ehrhardt, Marcos Luís (Romanitas - Revista de Estudos Grecolatinos, 2022)
One of the biggest, if not the main objective of a satire was to attack the evils of a society from this literary tool. A didactic-moralizing element, the satirical genre would have arisen, or would be motivated, from the observations of the vices, whether moral and/or social, or even better, from the criticism of behaviors considered distorted, deviant from what is considered as an ideal standard of conduct. Its main purpose: what it endorses, as well as what it criticizes of the Roman society of the first century of the Christian era, aiming to standardize a behavior for the citizen inhabitant of Rome, in the same way as for all the inhabitants of the Empire. Here, we make use of the verses written by a distinguished author who lived in the first century of the Christian era: it is Aulus Persius Flaccus, known only as Persius.